Effects of genotype and environment on forage yield, nutritive value and morphology of lablab (Lablab purpureus (L.) sweet) - Aleme, M.; Tamiru, T.; Alkhtib, A.; Assefa, Getnet; Kehaliew, A.; Tolemariam, T.; Mengistu, G.; Burton, E.; Janssens, G.P.J. (Elsevier, 2023)
The goal of the study is to determine the effect of genotype and environment on forage yield, forage nutritive value and to determine the relation between morphology and forage yield and nutritive value of lablab. Thirteen genotypes (one local and 12 improved) were replicated 3 times in a randomized complete block trial across three locations in Ethiopian lowlands namely, Bechi, Kite and Tepi. All forage samples were analyzed for dry matter (DM), crude protein (CP), and in vitro dry matter digestibility (IVDMD) using a combination of conventional nutritional analyses and near infrared reflectance spectroscopy. There was a significant (P < 0.001) effect of genotype, location and genotype*location on forage yield of DM, forage yield of CP, forage yield of IVDMD, CP, and IVDMD. The difference between means of minimum and maximum genotypes was 12.9 t/ha of DM, 3.12 t/ha CP, 8.22 t/ha IVDMD, 57 g/kg of CP and 56 g/kg of IVDMD. The correlation between plant morphology and forage yield and nutritive value was weak (r ≤ 0.41) in all locations and the combined data. Both genotype and location should be considered by the farmers when they decide to grow lablab for forage production. Morphological traits of lablab are not suitable to evaluate forage yield and nutritive value. Enhancing the awareness of farmers about the effect genetic-environment interaction effect of forage yield and nutritive value and the relation between morphology and yield and nutritive value would improve the uptake of lablab in mixed the farming system leading to more sustainable agricultural production.